Recommendations From the Common Terminology Panel of the American Council of Academic Physical Therapy. Issue 9 (19th June 2018) - Erickson, Mia; Birkmeier, Marisa; Booth, Melissa; Hack, Laurita M; Hartmann, Julie; Ingram, Debbie A; Jackson-Coty, Janet M; LaFay, Vicki L; Wheeler, Emma; Soper, Shawne
Abstract: Background: In 2015, the American Council for Academic Physical Therapy (ACAPT) developed 3 strategic initiative panels to address integrated clinical education, student readiness, and common terminology for physical therapist clinical education. Objective: The purpose of this paper is to describe the results of the work from the Common Terminology Panel. Design: This was a descriptive, consensus-based study. Methods: Using a consensus process and data that were collected from a review of literature, a document analysis of core and historical professional documents, focus group discussions, and an online open comment period, panel members developed a glossary for physical therapist clinical education. Results: The final glossary included 34 terms in 4 categories. The categories included clinical education infrastructure, sites, stakeholders, and assessment. The ACAPT Board of Directors approved the glossary in June 2017, and the ACAPT membership approved the glossary in October 2017. Limitations: The focus of the glossary was on physical therapist clinical education. A future, similar project should be undertaken for physical therapist assistant clinical education. Conclusion: This process resulted in a comprehensive glossary for physical therapist clinical education; changes to several current terms, including "internship" and "full-time clinical education experience"; and the addition of new terms, including "preceptor" and "site coordinator for clinical education." New terminology will provide standard language for consistent communication and a common framework for all stakeholders.